A clinical study of ectopic pregnancy in a tertiary care centre in Central India - Shrivastava, Mridula; Parashar, Hemlata; Modi, Jyoti Nath (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Ectopic pregnancy is an obstetric emergency with high morbidity and mortality. The incidence of ectopic pregnancy is on a rise globally. Risk factors and causes for ectopic pregnancy may vary with the setting and geographically. Methods: A retrospective analysis of all operated ectopic pregnancies over a 5-year period; between June 2011 to May 2016, was done. Surgically confirmed cases were included in this study and a detailed analysis of presenting symptoms, age, parity and high risk factors was carried out. Results: A total of 50 patients were operated for ectopic pregnancy at our hospital during the study period. Analysis was done for 47 of these due to incomplete data for 3 patients. Majority (62%) of patients belonged to the age group 20-29 years and were gravida 3 and above. Ninety two percent were ruptured ectopic. Sixty two percent ectopic pregnancies were on right side. The common presenting complaints were pain in abdomen (81%) and bleeding/spotting per vaginum (43%). The mean duration between onset of symptoms and reporting to hospital was one and a half day and the average time between admission to hospital and surgery was 9 hours. The ectopic pregnancies were managed surgically in all cases. No obvious risk factors were identified in 34% patients. Among the remaining, previous MTP (17%), previous ectopic (9%) and PID (7%) were identified risk factors. There was no mortality. Conclusions: Surgical treatment was done more often because of patients reporting late to the hospital. Screening of high risk cases, early diagnosis and early intervention reduces the morbidity and mortality in ectopic pregnancies.